Cannabidiol Affects the Bezold-Jarisch Reflex via TRPV1 and 5-HT3 Receptors and Has Peripheral Sympathomimetic Effects in Spontaneously Hypertensive and Normotensive Rats - Kossakowski, Rafał; Schlicker, Eberhard; Toczek, Marek; Weresa, Jolanta; Malinowska, Barbara (Frontiers in Pharmacology, 2019)
Cannabidiol (CBD) is a non-psychotropic constituent of Cannabis sativa L. It is suggested to be useful in hypertension. Under in vitro conditions it activates vanilloid TRPV1 and inhibits serotonin 5-HT3 receptors, i.e. receptors involved in the Bezold-Jarisch reflex stimulation. The aim of our study was to compare the cardiovascular effects of CBD in spontaneously hypertensive (SHR) and normotensive Wistar Kyoto (WKY) rats. Experiments were performed on conscious, urethane-anesthetized or pithed rats. In pithed SHR and WKY CBD increased heart rate (HR) and systolic blood pressure (SBP) and decreased diastolic BP (DBP) in a manner insensitive to adrenalectomy. Propranolol (nearly) abolished the CBD-induced increases in HR and SBP without affecting the decreases in DBP. Desipramine also reduced the CBD-induced effects on HR and SBP and further increased its effects on DBP. In anesthetized rats bolus i.v. injection of single doses of CBD induced short-lasting decreases in HR, SBP and DBP, stronger in SHR than in WKY and prevented by bilateral vagotomy. The CBD-induced fall in HR but not in BP was diminished by the TRPV1 receptor antagonist capsazepine and almost completely abolished if CBD was re-injected after previous administration. CBD reduced the Bezold-Jarisch reflex elicited by the 5-HT3 receptor agonist phenylbiguanide, but not that evoked by the TRPV1 agonist capsaicin. In conscious rats CBD did not affect cardiovascular parameters. In isolated left atria CBD decreased contractile force. Conclusions: Cannabidiol (1) induces the Bezold-Jarisch reflex via TRPV1 receptors (which undergo tachyphylaxis) more markedly in SHR than in WKY; (2) inhibits the Bezold-Jarisch reflex induced by activation of 5-HT3 but not TRPV1 receptors; (3) has peripheral sympathomimetic, (4) vasodilatory and (5) negative inotropic effects. The above properties of CBD should be taken under consideration when CBD is used for therapeutic purposes.